Ultra-lightweight and high-strength geopolymer-based composite material and preparation method thereof

By using industrial waste slag such as granulated blast furnace slag and microsilicon powder, combined with hollow microbeads and polyethylene fibers, an ultra-lightweight and high-strength earth polymer-based composite material is formed, which solves the problems of insufficient strength and environmental pollution of traditional concrete materials, and achieves efficient and environmentally friendly building materials applications.

CN116903390BActive Publication Date: 2025-03-14GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210655779.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-10
Publication Date
2025-03-14
Estimated Expiration
2042-06-10

AI Technical Summary

Technical Problem

The prior art is difficult to provide high-strength and low-weight concrete materials, and the carbon dioxide generated in traditional cement production pollutes the environment and requires an environmentally friendly and efficient alternative material.

Method used

Granulated blast furnace slag and microsilicon powder are used as raw materials, combined with hollow microbeads and polyethylene fibers, and ultra-lightweight high-strength earth polymer-based composite materials are formed through alkali excitation reactions, and the compressive strength and toughness of the material are improved through reasonable proportions and process treatments.

Benefits of technology

It realizes the lightweight and high-strength characteristics of the materials, reduces production costs, and reduces environmental pollution. It is suitable for the construction of structures such as super-high-rise buildings and large-span buildings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, and discloses an ultra-lightweight high-strength geopolymer-based composite material and a preparation method thereof. The ultra-lightweight high-strength geopolymer-based composite material comprises: a gelling material, hollow microspheres, an activator, and polyethylene fibers. The gelling material comprises: granulated blast furnace slag and microsilica powder; the activator comprises: water, sodium silicate, or a mixture of sodium silicate and sodium carbonate. The present invention uses sodium silicate or a mixture of sodium silicate and sodium carbonate as an activator, and the sodium silicate modulus of the activator is 1.2 to 1.6, so that the product has a higher early compressive strength. At the same time, the present invention uses hollow microspheres as lightweight micro-aggregates to make the composite material have properties such as light weight and high strength. The polyethylene fiber can improve the defects of low tensile strength and poor toughness of ordinary geopolymer matrices, play a role in crack prevention and toughening, and is conducive to promoting the construction and development of structures such as super high-rise buildings, large-span buildings, and offshore platforms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and more specifically, to an ultra-lightweight and high-strength geopolymer-based composite material and a preparation method thereof. Background Art

[0002] In recent years, with the increasing demand for structures such as super high-rise buildings, large-span buildings, and offshore platforms, the demand for high-strength, low-weight concrete has also increased. At the same time, with the vigorous promotion of prefabricated buildings in recent years, the use of high-strength, low-weight concrete to prepare prefabricated components can not only effectively reduce the cross-sectional size of the components, but also greatly reduce transportation costs and facilitate lifting and installation at the construction site.

[0003] On the other hand, with the development of modernization, the emission of industrial hazardous solid wastes such as fly ash, slag, and red mud has attracted people's attention. At the same time, the output of ordinary Portland cement in my country remains high. During the production of cement, the carbon dioxide greenhouse gas produced seriously pollutes the environment. Studies have shown that every ton of ordinary Portland cement produced will release 0.8 to 1.0 tons of greenhouse gas carbon dioxide. For this reason, we need to re-examine the development direction of the traditional cement industry.

[0004] Granulated blast furnace slag is a molten product with calcium aluminosilicate as the main component obtained when iron smelting pig iron in a blast furnace. It is an industrial solid waste slag obtained after water quenching and granulation. Most of it is glassy and has potential hydraulic cementitious properties. At the same time, granulated blast furnace slag has many advantages in use. Granulated blast furnace slag has a high activity index, a specific surface area of ​​about 400 or more, low heat and low alkali. As a mineral admixture in concrete construction, it can replace cement in equal amounts, reduce costs, and improve quality. More importantly, it solves technical problems such as high heat, high alkali, and cracks in the construction of some major projects. In addition, as an industrial solid waste, blast furnace slag, if piled up in the open air all year round, will not only occupy a large amount of land, but also cause serious pollution to the atmosphere, soil and groundwater systems due to dust and heavy metal ions leached with rainwater. In addition, microsilica powder is obtained by recycling industrial dust generated during the production of silicon-containing alloys. Both have a wide range of sources, which can realize the recycling of industrial waste slag, meet the green environmental protection requirements of energy conservation and emission reduction, and are suitable for promotion. Therefore, geopolymer materials (geopolymers) prepared with granulated blast furnace slag and other industrial waste slag as raw materials as cementitious materials to replace traditional silicate cement have significant advantages in green development.

[0005] In summary, it is necessary to develop an ultra-lightweight and high-strength geopolymer-based composite material with granulated blast furnace slag as the main raw material. Summary of the invention

[0006] To solve the above problems, one of the purposes of the present invention is to provide an ultra-lightweight and high-strength geopolymer-based composite material. The product uses hollow microspheres as lightweight micro-aggregates, so that the composite material has properties such as light weight and high strength. Polyethylene fibers can improve the defects of low tensile strength and poor toughness of ordinary geopolymer matrices, and play a role in crack prevention and toughening. Therefore, this product has the advantages of low apparent density and strong compressive strength, which is conducive to promoting the construction and development of structures such as super high-rise buildings, large-span buildings, and offshore platforms.

[0007] The second purpose of the present invention is to provide a method for preparing an ultra-lightweight and high-strength geopolymer-based composite material. The method has reasonable raw material selection and dosage ratio. The raw materials used are granulated blast furnace slag and microsilica powder, both of which are widely available and can realize the recycling of industrial waste slag. It meets the green environmental protection requirements of energy saving and emission reduction and is suitable for promotion.

[0008] To achieve the above object, the technical solution of the present invention is as follows:

[0009] An ultra-lightweight high-strength geopolymer-based composite material comprises: a gelling material, hollow microspheres, an activator, and polyethylene fibers. The gelling material comprises: granulated blast furnace slag and microsilica powder; the activator comprises: water, sodium silicate, or a mixture of sodium silicate and sodium carbonate.

[0010] Furthermore, the polymer-based composite material package also includes an additive, and the additive includes barium chloride and / or a defoaming agent.

[0011] Furthermore, the geopolymer-based composite material comprises the following components by weight: 690-730 parts of gelling material, 290-320 parts of hollow microspheres, 305-480 parts of activator, 0-11 parts of admixture, and 0.1-10 parts of polyethylene fiber.

[0012] Furthermore, the activator comprises the following components: water, sodium silicate or a mixture of sodium silicate and sodium carbonate. The sodium silicate in the activator is sodium silicate with adjusted modulus. Preferably, the modulus of the sodium silicate in the activator is 1.2 to 1.6.

[0013] In addition, the weight ratio of sodium oxide to gelling material in the sodium silicate is (0.05-0.08):1, the weight ratio of sodium oxide to gelling material in the sodium carbonate is (0-0.02):1, and the weight ratio of water to gelling material in the activator is (0.28-0.34):1. The calculation method of the sodium oxide content in the sodium silicate is:

[0014]

[0015] A1 is the sodium oxide content in sodium silicate, B is the molecular weight of sodium oxide, C1 is the mass of sodium silicate (solid), and D1 is the molecular weight of sodium silicate;

[0016] The calculation method of sodium oxide content in sodium carbonate is:

[0017]

[0018] A2 is the sodium oxide content in sodium carbonate, C2 is the mass of sodium carbonate, and D2 is the molecular weight of sodium carbonate.

[0019] The weight ratio of water to gelling material in the activator refers to the weight ratio of water to gelling material in the prepared activator, and the water in the activator includes the water added during preparation and the water contained in the raw materials used to prepare the activator.

[0020] The modulus of sodium silicate refers to the ratio of the amount of substance of SiO2 and Na2O. The sodium silicate in the activator is obtained by dissolving the sodium silicate solid and adjusting the modulus to the required range through sodium hydroxide. The finished sodium silicate product model is SP50, with a silicon dioxide content of 29.99%, a sodium oxide content of 13.75%, and a water content of 56.26%. Studies have found that the activator concentration and the activator modulus are key factors affecting the performance of geopolymers, and the modulus plays an important role in generating precursors and final products. At present, the suitable modulus of the activator reported in most literatures is within the range of 1.2 to 1.6. If the modulus is too low, the mechanical strength of the geopolymer prepared therefrom will be insufficient, and the possibility of alkali return in the later stage will be increased due to the low modulus. When the modulus gradually increases, the degree of polymerization of the geopolymer deepens, the density of the product gradually increases, and the compressive strength increases. If the modulus is too high, as the modulus continues to increase, the viscosity of the activator solution increases, and the bubbles introduced during the product preparation process are difficult to discharge, resulting in a decrease in the density of the product. In addition, excess SiO2 will hinder the reaction of the precursor, thereby reducing the compressive strength of the product.

[0021] Preferably, the cementitious material comprises the following components by weight: 690-725 parts of granulated blast furnace slag and 95-105 parts of microsilica powder; the admixture comprises the following components by weight: 0-10 parts of barium chloride and 0-1 part of defoaming agent.

[0022] Preferably, the particle size of the granulated blast furnace slag is 1-45 μm, the particle size of the microsilica powder is 0.1-1 μm, the length of the polyethylene fiber is 12-21 mm, and the diameter of the polyethylene fiber is 1-25 μm.

[0023] Under alkali excitation conditions, slag and microsilica powder can react to form geopolymers. Since slag is a highly active inorganic aluminosilicate, it coagulates and hardens quickly under alkali excitation conditions, especially under high temperature conditions, the alkali excitation reaction rate is difficult to control, which limits the promotion and application of geopolymers. However, this patent uses barium chloride as a retarder. Adding 0 to 10 parts of barium chloride can effectively slow down the reaction rate of geopolymer slurry and enhance the compressive strength of its hardened body.

[0024] Polyethylene fiber is a reinforcing material. After special surface treatment technology, it has strong acid and alkali resistance, weak thermal conductivity, and extremely stable chemical properties. It is often used in geopolymers, concrete or mortar to prevent and inhibit the formation and development of cracks, and greatly improve the crack resistance, anti-seepage performance, impact resistance and earthquake resistance of geopolymers, concrete or mortar.

[0025] Preferably, the defoaming agent is a commercially available polyether defoaming agent, which is used to increase the density of concrete to improve its mechanical properties and durability.

[0026] Furthermore, the hollow microbeads include: hollow microbeads with a first particle size and hollow microbeads with a second particle size; the feed ratio of the hollow microbeads with the first particle size to the hollow microbeads with the second particle size is 1:(0.5-0.6).

[0027] Preferably, the density of the hollow microspheres of the first particle size is 800 to 900 m 3 / kg, particle size is 50-300 μm, compressive strength is 15-20 MPa; the density of the second particle size hollow microspheres is 700-760 m 3 / kg, particle size is 5-50μm, and compressive strength is 120-125MPa.

[0028] Preferably, the first-size hollow microspheres are hollow ceramic microspheres with an average particle size of 180 μm and a density of 850 kg / m 3 The second particle size hollow microspheres are hollow glass microspheres with an average particle size of 25 μm and a density of 700 to 760 kg / m 3 , the compressive strength is 124MPa. In the building materials industry, hollow microspheres are often used as lightweight aggregates to make composite materials have properties such as light weight and high strength. At the same time, it can improve the fluidity of mortar, reduce material shrinkage, improve the comprehensive performance of products, and reduce comprehensive production costs.

[0029] A method for preparing an ultra-lightweight and high-strength geopolymer-based composite material, characterized by comprising the following steps:

[0030] S01. Add the gelling material, hollow microspheres and admixtures into a forced mixer according to the proportion, stir for 3 to 6 minutes to obtain a dry mix, and set aside;

[0031] S02, taking additional water, sodium silicate or a mixture of sodium silicate and sodium carbonate according to the proportion, mixing and stirring for 3 to 5 minutes to obtain an activator solution, cooling and setting aside, wherein the additional water refers to the water that needs to be added when preparing the activator;

[0032] S03, adding the activator solution prepared in S02 to the dry blend prepared in S01, mixing and stirring for 2 to 5 minutes; adding polyethylene fiber, mixing and stirring for 2 to 4 minutes, obtaining a slurry, and setting aside;

[0033] S04, pouring the slurry obtained in step S03 into a mold, vibrating it, sealing it and letting it stand for 24 hours, demoulding it, and curing it at room temperature to obtain an ultra-lightweight and high-strength geopolymer-based composite material.

[0034] Preferably, the preparation method of the activator in step S02 is: dissolving the sodium silicate product in water according to a proportion, adding sodium hydroxide solution to adjust the modulus of the activator to 1.2-1.6 to obtain a sodium silicate solution, then dissolving carbonic acid in the sodium silicate solution according to a proportion, stirring evenly, cooling to room temperature, and setting aside.

[0035] Preferably, the room temperature curing method in step S04 includes but is not limited to: room temperature curing in an underwater environment and room temperature curing in a plastic film sealed environment.

[0036] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0037] 1. The raw materials and dosage ratio of the ultra-lightweight and high-strength geopolymer-based composite material of the present invention are reasonably selected. Hollow microspheres are used as lightweight micro-aggregates to make the composite material have properties such as light weight and high strength. Polyethylene fibers can improve the defects of ordinary geopolymer matrices such as low tensile strength and poor toughness, and play a role in crack prevention and toughening.

[0038] 2. The present invention uses sodium silicate or a mixture of sodium silicate and sodium carbonate as an activator. The modulus of the sodium silicate of the activator is 1.2 to 1.6, so that the product has a higher early compressive strength and reduces the possibility of a lower modulus increasing the possibility of alkali return in the later period.

[0039] 3. The present invention adopts barium chloride and defoaming agent as admixtures, and then flexibly selects granulated blast furnace slag, microsilica powder, alkaline activator, etc., so that the fluidity performance index of the geopolymer-based composite material can reach a stable and adjustable effect. At the same time, the gas content of the product is reduced, and the workability of the product is improved, thereby greatly improving the comprehensive performance of the geopolymer-based composite material.

[0040] 4. The granulated blast furnace slag used as the raw material of the present invention is a molten product with calcium aluminosilicate as the main component obtained when the iron smelting plant smelts pig iron in the blast furnace, and is an industrial solid waste slag obtained after water quenching and granulation; the microsilica powder used is obtained by recycling the industrial dust generated in the production of silicon-containing alloys. Both have a wide range of sources, can realize the recycling of industrial waste slag, meet the green environmental protection requirements of energy saving and emission reduction, and are suitable for promotion. DETAILED DESCRIPTION

[0041] The present invention is specifically described below by way of examples. It should be noted that these examples are for illustrating the present invention and do not limit the scope of the present invention.

[0042] Unless otherwise specified, the technical means used in the embodiments of the present invention are conventional means well known to those skilled in the art, and the raw materials and equipment used can be obtained from commercial channels.

[0043] 1. Experimental Materials

[0044] The raw material information used in the examples and comparative examples of the present invention is shown in Table 1.

[0045] Table 1 Raw materials used in Examples and Comparative Examples

[0046]

[0047]

[0048] 2. Performance Testing

[0049] Compressive strength: The ultra-lightweight high-strength cement-based composite material specimens were subjected to uniaxial compression loading tests using a material compression testing machine to obtain their axial compressive strength. The compressive strength test method refers to the relevant provisions of the "Standard for Basic Performance Test Methods of Building Mortar" JGJ / T70-2009.

[0050] Example 1

[0051] The specific construction steps of an ultra-lightweight and high-strength geopolymer-based composite material are as follows:

[0052] S01, take 708 parts of granulated blast furnace slag, 101 parts of microsilica powder, 193 parts of hollow ceramic microspheres, 111 parts of hollow glass microspheres, 8 parts of barium chloride, and 0.8 parts of defoamer, add them into a forced mixer, stir for 3 to 6 minutes, and obtain a dry mix for standby use. The ratio of hollow ceramic microspheres to hollow glass microspheres is 1:0.575.

[0053] S02, take 276 parts of sodium silicate finished product, add 103 parts of additional water into a plastic container, stir for 5 minutes, add 26 parts of sodium hydroxide and stir and mix evenly to obtain a sodium silicate solution with a modulus of 1.47, wherein the ratio of sodium oxide to gelling material in the sodium silicate is 0.072:1, and the weight ratio of water to gelling material in the activator is 0.32:1.

[0054] S03, adding the activator solution prepared in S02 to the dry blend prepared in S01, mixing and stirring for 2 to 5 minutes; adding 4.75 parts of polyethylene fiber, mixing and stirring for 2 to 4 minutes to obtain slurry, which is set aside;

[0055] S04, pouring the slurry obtained in step S03 into a cubic mold with a size of 70.7 mm×70.7 mm×70.7 mm, vibrating it on a vibration table for 60 seconds after the slurry is filled in, sealing it and standing it outdoors for 24 hours for curing, then removing the mold, and curing it at room temperature in a water environment to obtain an ultra-lightweight and high-strength geopolymer-based composite material.

[0056] Example 2

[0057] The specific construction steps of an ultra-lightweight and high-strength geopolymer-based composite material are as follows:

[0058] S01, take 708 parts of granulated blast furnace slag, 101 parts of microsilica powder, 193 parts of hollow ceramic microspheres, 111 parts of hollow glass microspheres, 8 parts of barium chloride, 0.8 parts of defoamer, add them into a forced mixer, stir for 3 to 6 minutes, and obtain a dry mix for standby use. The ratio of hollow ceramic microspheres to hollow glass microspheres is 1:0.575.

[0059] S02, take 196 parts of sodium silicate finished product, add 148 parts of additional water into a plastic container, stir for 5 minutes, add 28 parts of sodium hydroxide and stir and mix evenly to obtain a sodium silicate solution with a modulus of 1.25, wherein the ratio of sodium oxide to gelling material in the sodium silicate is 0.060:1, and the weight ratio of water to gelling material in the activator is 0.32:1.

[0060] S03, adding the activator solution prepared in S02 to the dry blend prepared in S01, mixing and stirring for 2 to 5 minutes; adding 4.75 parts of polyethylene fiber, mixing and stirring for 2 to 4 minutes to obtain slurry, which is set aside;

[0061] S04, pouring the slurry obtained in step S03 into a cubic mold with a size of 70.7 mm×70.7 mm×70.7 mm, vibrating it on a vibration table for 60 seconds after the slurry is filled in, sealing it and standing it outdoors for 24 hours for curing, then removing the mold, and curing it at room temperature in a plastic film sealed environment to obtain an ultra-lightweight and high-strength geopolymer-based composite material.

[0062] Example 3

[0063] The specific construction steps of an ultra-lightweight and high-strength geopolymer-based composite material are as follows:

[0064] S01, take 708 parts of granulated blast furnace slag, 101 parts of microsilica powder, 193 parts of hollow ceramic microspheres, 111 parts of hollow glass microspheres, 8 parts of barium chloride, 0.8 parts of defoamer, add them into a forced mixer, stir for 3 to 6 minutes, and obtain a dry mix for standby use. The ratio of hollow ceramic microspheres to hollow glass microspheres is 1:0.575.

[0065] S02, take 180 parts of sodium silicate finished product, add 157 parts of additional water into a plastic container, stir for 5 minutes, add 26 parts of sodium hydroxide and stir and mix evenly to obtain a sodium silicate solution with a modulus of 1.25, and set aside. Then take 21 parts of sodium carbonate and add them to the sodium silicate solution with a modulus of 1.25, stir and mix evenly to obtain a mixed solution of sodium carbonate and sodium silicate with a modulus of 1.25. The weight ratio of sodium oxide to gelling material in sodium silicate is 0.056:1, the weight ratio of sodium oxide to gelling material in sodium carbonate is 0.015:1, and the weight ratio of water to gelling material in the activator is 0.32:1.

[0066] S03, adding the activator solution prepared in S02 to the dry blend prepared in S01, mixing and stirring for 2 to 5 minutes; adding 4.75 parts of polyethylene fiber, mixing and stirring for 2 to 4 minutes to obtain slurry, which is set aside;

[0067] S04, pouring the slurry obtained in step S03 into a cubic mold with a size of 70.7 mm×70.7 mm×70.7 mm, vibrating it on a vibration table for 60 seconds after the slurry is filled in, sealing it and standing it outdoors for 24 hours for curing, then removing the mold, and curing it at room temperature in a plastic film sealed environment to obtain an ultra-lightweight and high-strength geopolymer-based composite material.

[0068] Example 4

[0069] The specific construction steps of an ultra-lightweight and high-strength geopolymer-based composite material are as follows:

[0070] S01, take 708 parts of granulated blast furnace slag, 101 parts of microsilica powder, 193 parts of hollow ceramic microspheres, 111 parts of hollow glass microspheres, 8 parts of barium chloride, 0.8 parts of defoamer, add them into a forced mixer, stir for 3 to 6 minutes, and obtain a dry mix for standby use. The ratio of hollow ceramic microspheres to hollow glass microspheres is 1:0.575.

[0071] S02, take 215 parts of sodium silicate finished product, add 137 parts of additional water into a plastic container, stir for 5 minutes, add 20 parts of sodium hydroxide, stir and mix evenly, obtain a sodium silicate solution with a modulus of 1.5, and set aside. Then take 21 parts of sodium carbonate and add them to the sodium silicate solution with a modulus of 1.5, stir and mix evenly, and obtain a mixed solution of sodium carbonate and sodium silicate with a modulus of 1.5. The ratio of sodium oxide to gelling material in sodium silicate is 0.056:1, the ratio of sodium oxide to gelling material in sodium carbonate is 0.015:1, and the weight ratio of water to gelling material in the activator is 0.32:1.

[0072] S03, adding the activator solution prepared in S02 to the dry blend prepared in S01, mixing and stirring for 2 to 5 minutes; adding 4.75 parts of polyethylene fiber, mixing and stirring for 2 to 4 minutes to obtain slurry, which is set aside;

[0073] S04, pouring the slurry obtained in step S03 into a cubic mold with a size of 70.7 mm×70.7 mm×70.7 mm, vibrating it on a vibration table for 60 seconds after the slurry is filled in, sealing it and standing it outdoors for 24 hours for curing, then removing the mold, and curing it at room temperature in a plastic film sealed environment to obtain an ultra-lightweight and high-strength geopolymer-based composite material.

[0074] Example 5

[0075] The specific construction steps of an ultra-lightweight and high-strength geopolymer-based composite material are as follows:

[0076] S01. Take 708 parts of granulated blast furnace slag, 101 parts of microsilica powder, 193 parts of hollow ceramic microspheres, 111 parts of hollow glass microspheres, and 8 parts of barium chloride, add them into a forced mixer, stir for 3 to 6 minutes, and obtain a dry mix for standby use. The ratio of hollow ceramic microspheres to hollow glass microspheres is 1:0.575.

[0077] S02, take 196 parts of sodium silicate finished product, add 148 parts of additional water into a plastic container, stir for 5 minutes, add 28 parts of sodium hydroxide and stir and mix evenly to obtain a sodium silicate solution with a modulus of 1.25, wherein the ratio of sodium oxide to gelling material in the sodium silicate is 0.06:1, and the weight ratio of water to gelling material in the activator is 0.32:1.

[0078] S03, adding the activator solution prepared in S02 to the dry blend prepared in S01, mixing and stirring for 2 to 5 minutes; adding 4.75 parts of polyethylene fiber, mixing and stirring for 2 to 4 minutes to obtain slurry, which is set aside;

[0079] S04, pouring the slurry obtained in step S03 into a cubic mold with a size of 70.7 mm×70.7 mm×70.7 mm, vibrating it on a vibration table for 60 seconds after the slurry is filled in, sealing it and standing it outdoors for 24 hours for curing, then removing the mold, and curing it at room temperature in a plastic film sealed environment to obtain an ultra-lightweight and high-strength geopolymer-based composite material.

[0080] Comparative Example 6

[0081] The specific construction steps of an ultra-lightweight and high-strength geopolymer-based composite material are as follows:

[0082] S01, take 708 parts of granulated blast furnace slag, 101 parts of microsilica powder, 193 parts of hollow ceramic microspheres, 111 parts of hollow glass microspheres, 8 parts of barium chloride, 0.8 parts of defoamer, add them into a forced mixer, stir for 3 to 6 minutes, and obtain a dry mix for standby use. The ratio of hollow ceramic microspheres to hollow glass microspheres is 1:0.575.

[0083] S02, take 196 parts of sodium silicate finished product, add 148 parts of additional water into a plastic container, stir for 5 minutes, add 28 parts of sodium hydroxide and stir and mix evenly to obtain a sodium silicate solution with a modulus of 1.25, wherein the ratio of sodium oxide to gelling material in the sodium silicate is 0.06:1, and the weight ratio of water to gelling material in the activator is 0.32:1.

[0084] S03, adding the activator solution prepared in S02 to the dry mixed material prepared in S01, mixing and stirring for 2 to 5 minutes to obtain a slurry, which is set aside;

[0085] S04, pouring the slurry obtained in step S03 into a cubic mold with a size of 70.7 mm×70.7 mm×70.7 mm, vibrating it on a vibration table for 60 seconds after the slurry is filled in, sealing it and standing it outdoors for 24 hours for curing, then removing the mold, and curing it at room temperature in a plastic film sealed environment to obtain an ultra-lightweight and high-strength geopolymer-based composite material.

[0086] Comparative Example 7

[0087] The specific construction steps of an ultra-lightweight and high-strength geopolymer-based composite material are as follows:

[0088] S01, take 708 parts of granulated blast furnace slag, 101 parts of microsilica powder, 193 parts of hollow ceramic microspheres, 111 parts of hollow glass microspheres, 8 parts of barium chloride, 0.8 parts of defoamer, add them into a forced mixer, stir for 3 to 6 minutes, and obtain a dry mix for standby use. The ratio of hollow ceramic microspheres to hollow glass microspheres is 1:0.575.

[0089] S02, take 273 parts of sodium silicate finished product, add 103 parts of additional water into a plastic container, stir for 5 minutes, add 14 parts of sodium hydroxide and stir and mix evenly to obtain a sodium silicate solution with a modulus of 1.75, wherein the ratio of sodium oxide to gelling material in the sodium silicate is 0.06:1, and the weight ratio of water to gelling material in the activator is 0.32:1.

[0090] S03, adding the activator solution prepared in S02 to the dry blend prepared in S01, mixing and stirring for 2 to 5 minutes; adding 4.75 parts of polyethylene fiber, mixing and stirring for 2 to 4 minutes to obtain slurry, which is set aside;

[0091] S04, pouring the slurry obtained in step S03 into a cubic mold with a size of 70.7 mm×70.7 mm×70.7 mm, vibrating it on a vibration table for 60 seconds after the slurry is filled in, sealing it and standing it outdoors for 24 hours for curing, then removing the mold, and curing it at room temperature in a plastic film sealed environment to obtain an ultra-lightweight and high-strength geopolymer-based composite material.

[0092] The ultra-lightweight and high-strength geopolymer-based composite materials prepared in Examples 1 to 5 and Comparative Examples 6 to 7 of the present invention were used as experimental objects to test the performance of the concrete in the examples. The test was conducted with reference to GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete". The test results of the ultra-lightweight and high-strength geopolymer-based composite materials in Examples 1 to 5 and Comparative Examples 6 to 7 are shown in Table 2 below:

[0093] Table 2 Test results of ultra-lightweight and high-strength geopolymer-based composite materials

[0094]

[0095] It can be seen from Table 2 that the 28d compressive strength of Examples 2 and 3 is the highest, while the 28d compressive strength of the same type of geopolymer-based composite materials on the market is mostly 40-50 MPa. Therefore, the geopolymer-based composite material provided by the present invention has the characteristics of high compressive strength. At the same time, it can be seen from Examples 2-3 that in addition to having high compressive strength, the apparent density of the geopolymer-based composite material provided by the present invention is 1466 kg / m 3 The apparent density of other similar geopolymer products on the market is mostly between 2200 and 2700 kg / m 3 Thus, it can be seen that the present invention provides a lightweight geopolymer-based composite material.

[0096] In addition, by comparing Example 2 with Example 5, it can be found that the addition of a defoaming agent can also improve the strength of the product to a certain extent. This is because the defoaming agent can improve the air content in the geopolymer-based composite material, improve the workability of the product, reduce bubbles on the surface of the product, and thus improve the strength of the product.

[0097] In addition, by comparing Example 2 with Comparative Example 6, it can be clearly seen that without the addition of polyethylene fiber, the compressive strength of the product is greatly affected. Compared with Example 2, the 7d compressive strength of the product of Comparative Example 6 is reduced by 21.46%, and the 28d compressive strength is reduced by 25.87%. Therefore, polyethylene fiber can enhance the strength of the composite material, improve the defects of ordinary geopolymer matrix such as low tensile strength and poor toughness, and play a role in crack prevention and toughening.

[0098] Finally, the contents of each component in Example 2 and Comparative Example 7 are the same, and there is only a difference in the modulus of sodium silicate in the activator, wherein the modulus of sodium silicate in Example 2 is 1.25, and the modulus of sodium silicate in Comparative Example 7 is 1.75. However, the 7d compressive strength of Example 2 is 9.81% higher than that of Comparative Example 7, and the 28d compressive strength is 18.42% higher. Therefore, it can be known that when the sodium silicate modulus ratio is 1.25, the compressive strength of the geopolymer-based composite material is the highest.

[0099] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description, and it is not necessary and impossible to list all the embodiments here. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. An ultra-lightweight and high-strength geopolymer-based composite material, characterized in that: The geopolymer-based composite material comprises the following components by weight: 690-730 parts of gelling material, 290-320 parts of hollow microspheres, 305-480 parts of activator, 0.1-10 parts of polyethylene fiber, and 0-11 parts of admixture; The cementitious material comprises: 690-725 parts of granulated blast furnace slag and 95-105 parts of microsilica powder; the admixture comprises barium chloride and / or a defoamer; the activator comprises: water, and also sodium silicate or a mixture of sodium silicate and sodium carbonate; The weight ratio of sodium oxide to gelling material in the sodium silicate is (0.056-0.060):1, the weight ratio of sodium oxide to gelling material in the sodium carbonate is 0.015:1, and the weight ratio of water to gelling material in the activator is 0.32:1; The modulus of sodium silicate in the activator is 1.

25.

2. The ultra-lightweight and high-strength geopolymer-based composite material according to claim 1, characterized in that: The cementitious material includes the following components by weight: 708 parts of granulated blast furnace slag and 101 parts of microsilica powder; the admixture includes the following components by weight: 8 parts of barium chloride and 0.8 parts of defoaming agent.

3. The ultra-lightweight and high-strength geopolymer-based composite material according to claim 2, characterized in that: The particle size of the granulated blast furnace slag is 1 to 45 μm, the particle size of the microsilica powder is 0.1 to 1 μm, the length of the polyethylene fiber is 12 to 21 mm, and the diameter of the polyethylene fiber is 1 to 25 μm.

4. The ultra-lightweight and high-strength geopolymer-based composite material according to claim 3, characterized in that: The hollow microbeads include: hollow microbeads with a first particle size and hollow microbeads with a second particle size; the feed ratio of the hollow microbeads with the first particle size to the hollow microbeads with the second particle size is 1:(0.5-0.6).

5. The ultra-lightweight and high-strength geopolymer-based composite material according to claim 4, characterized in that: The density of the hollow microspheres with the first particle size is 800 to 900 m 3 / kg, particle size is 50-300μm, compressive strength is 15-20MPa; the density of the second particle size hollow microspheres is 700-760m 3 / kg, particle size is 5-50μm, and compressive strength is 120-125MPa.

6. A method for preparing an ultra-lightweight and high-strength geopolymer-based composite material, characterized in that: The method for preparing the ultra-lightweight and high-strength geopolymer-based composite material according to any one of claims 1 to 5 comprises the following steps: S01. Add the gelling material, hollow microspheres and admixtures into a forced mixer according to the proportion, stir for 3 to 6 minutes to obtain a dry mix, and set aside; S02, taking additional water, sodium silicate or a mixture of sodium silicate and sodium carbonate according to the proportion, mixing and stirring for 3 to 5 minutes to obtain an activator solution, and cooling for standby use; S03, adding the activator solution prepared in S02 to the dry blend prepared in S01, mixing and stirring for 2 to 5 minutes; adding polyethylene fiber, mixing and stirring for 2 to 4 minutes, obtaining a slurry, and setting aside; S04, pouring the slurry obtained in step S03 into a mold, vibrating it, sealing it and letting it stand for 24 hours, demoulding it, and curing it at room temperature to obtain an ultra-lightweight and high-strength geopolymer-based composite material.

Citation Information

Patent Citations

  • Fiber-reinforced glass bead geological polymer and preparation method thereof

    CN107344831A